2023
DOI: 10.1128/mbio.02123-23
|View full text |Cite
|
Sign up to set email alerts
|

Inbred SJL mice recapitulate human resistance to Cryptococcus infection due to differential immune activation

M. J. Davis,
R. E. Martin,
G. M. Pinheiro
et al.

Abstract: Cryptococcosis remains a significant threat to human health. While the popular C57BL/6J mouse model of cryptococcosis has some advantages, there are some serious shortcomings that limit the ability of researchers to address the disease. Since humans are resistant to environmental cryptococcal infection until rendered immunodeficient while C57BL/6J mice are innately susceptible, we screened 15 inbred mouse strains for resistance to Cryptococcus infection. The SJL/J mouse strain was unusu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Additional advantages are the relatively low maintenance costs, the ease of handling mice, and the availability of many inbred and transgenic mouse strains [48]. Past studies have shown differences between inbred strains in survival rates, inoculum doses (even when administered via the same route), yielding differences in susceptibility, and disease progression [93][94][95]. C57BL/6, A/J, CBA/J, DBA/J, and BALB/c mouse strains are most often used to study experimental Cryptococcus infection models [96][97][98].…”
Section: Mus Musculus (Mice)mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional advantages are the relatively low maintenance costs, the ease of handling mice, and the availability of many inbred and transgenic mouse strains [48]. Past studies have shown differences between inbred strains in survival rates, inoculum doses (even when administered via the same route), yielding differences in susceptibility, and disease progression [93][94][95]. C57BL/6, A/J, CBA/J, DBA/J, and BALB/c mouse strains are most often used to study experimental Cryptococcus infection models [96][97][98].…”
Section: Mus Musculus (Mice)mentioning
confidence: 99%
“…C57BL/6, A/J, CBA/J, DBA/J, and BALB/c mouse strains are most often used to study experimental Cryptococcus infection models [96][97][98]. A study by Davis et al indicated discrepancies between the C57BJ/6J, FVB/J, and SJL/J strains observed due to differences in immune response [95]. Another study performed by Zaragoza et al observed immunological differences in the susceptibility of CBA/J and BALB/C strains when injected with IT but not when injected with IV [94].…”
Section: Mus Musculus (Mice)mentioning
confidence: 99%
“…Integration of these findings into a coherent model is limited by the use of diverse cryptococcal isolates, including a laboratory strain (B3501), an avirulent strain (LW10), or a highly virulent strain (H99). Finally, all of these studies were performed in the naturally susceptible C57BL/6 inbred mice that developed progressive C. neoformans infection in the presence of a functional Card9 gene [ 20 , 21 ]. Thus, to gain further insight into the role of Card9 during the pathogenesis of cryptococcal pneumonia we challenged wild-type and Card9-mutant mice on the Balb/c background with a moderately virulent serotype D strain of C. neoformans (52D) using well-established experimental conditions and analyzed host resistance and immune responses at serial time points up to day 28 post-infection.…”
Section: Introductionmentioning
confidence: 99%